PENERAPAN GROUP TO GROUP EXCHANGE UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR MATEMATIKA SISWA KELAS XA SMA NEGERI I TANJUNGSARI GUNUNGKIDUL - Haryanto Haryanto; Benedictus Kusmanto (UNION: Jurnal Ilmiah Pendidikan Matematika, 2014)
The purpose of this research is to know the result and active learning of the students in XA grade of SMA Negeri 1 Tanjungsari Gunungkidul using active learning method Group to Group Exchange (GGE) type. This research is Classroom Action Research (CAR) conducted collaboratively. Subjects of this research are XA students of SMA Negeri 1 Tanjungsari Gunungkidul 31 students. Data of active learning student was collected through observation. Data of students' mathematics learning outcomes were collected through testing and documentation. Observations indicate increased student activity term I 68.8% and term II 78%. Increased students' mathematics learning outcomes viewed from the average value and completeness KKM. The average value of 74.90 with 17 pre- term students who completed, the term I 78.26 with 21 student who completed, and term II of 83.81 with 24 students who completed. Researcher hoped teachers can apply GGE models.